Robert Aleksander Maryks. The Jesuit Order as a Synagogue of Jews: Jesuits of Jewish Ancestry and Purity-of-Blood Laws in the Early Society of Jesus. Studies in Medieval and Reformation Traditions 146 - Bell, Dean Phillip (Studies in Christian-Jewish Relations, 2013)
No abstract is available.